Interrelations of vegetal cover, silicophytolith content and pedogenesisof Typical Argiudolls of the Pampean Plain, Argentina - Borrelli, Natalia Lorena (2008)
Knowledge of the origin, evolution and weathering of Pampean soils is still limited. There are few prior studies of silicophytoliths, even though they could be important pedogenetic indicators that provide information about the role of amorphous silica in the reestablishment of soil structure. The aim of this work is to determine the silicophytolith content in Typical Argiudolls of the Pampean Plain, Argentina, its relation with vegetal cover and its effect on pedogenesis. We worked in three plots with different vegetal cover: grasses and shelter-belt plantations of Acacia melanoxylon – Celtis tala and Eucalyptus globulus – Celtis tala .In the study area, morphological characterization and particle size distribution analysis of soils were completed, and pH and organic matter content were determined. The heavy liquid separation was realized with sodium polytungstate ( δ =2.3 g/cm 3 ) and an average of around 500 mineral grains were counted under optical microscope for the quali-quantitative analysis. There were no differences between pro fi les with respect to their morphological properties, organic matter content and particle size distribution, except for the higher organic horizon development of the forest plots as compared with the grass plot. The silicophytolith content was higher in the forest plots than in the grass one; within each pro fi le, this fraction content decreased from the surface (63 – 40%) to the subsurface levels (23 – 5%) of soils. This decrease parallels the pieces of amorphous silica ( b 7.5 μ m) distribution in all plots analyzed. Afforestation over the past 50 years does not affect either the morphological or the physico-chemical properties of soils. These forest species, through the organic horizons, preserve soil conditions, which insures a higher representativity of silicophytoliths in comparison with the grass plot.